Kampanye Bisnis Islami : Konsep Pembudayaan dan Pemberdayaan Ekonomi Islam di Waroeng Steak & Shake Yogyakarta - Arin Setiyowati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2019)
AbstrakThis study aims to determine whether How is the spirit of Islamiceconomics is able to be a catalyst in the dimensions of service quality inbranch Waroeng Steak and Shake (WS), Yogyakarta with a researchfocus on the strategies of acculturation and economic empowerment of thespirit of Islam. The method used is qualitative, with the approach ofobservation and interviews with informants internal objects and visitors indepthresearch, the technique of non-purposive random sampling.Simultaneously, it can be concluded that the business strategy with the P2approach (acculturation and empowerment) of Islamic economics (one ofthem through Islamic business ethics) can be value added to WaroengSteak and Shake(WS) in the eyes of the customer, and the multipliereffect of the internal WS with increasing turnover (size material),increasing the power of faith (the size of the non-material) for allemployees. While no doubt also customer satisfaction and mostimportantly, the social effects of the mustadz'afin parties (social)automatically also feel its impact.Kata Kunci : Waroeng Steak and Shake, Acculturation, Empowerment,Islamic Islamic business ethics.